2018
DOI: 10.2147/ijn.s166438
|View full text |Cite
|
Sign up to set email alerts
|

Lumbrokinase/paclitaxel nanoparticle complex: potential therapeutic applications in bladder cancer

Abstract: BackgroundLumbrokinase (LK) is an enzyme complex with antithrombotic, antioxidant, antitumor, and immunomodulatory effects. It has been extensively studied and used in clinical anti-tumor therapy. However, its half-life is short, its bioavailability is low, and its toxicity and side effects are great, which greatly limit its clinical application. Therefore, LK is often combined with other drugs (such as immune agents, hormones, or Chinese herbal medicine) to reduce its dosage and side effects and to improve it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Hu et al skillfully used block copolymer PEG-b-(PELG-g-(PZLL-r-PLL)) as a nanocarrier to deliver lumbrokinase (LK) with PTX and avoided the great toxicity and ensure sustained release in bladder. In addition, LK/PTX/PEG- b-(PELG-g-(PZLL-r-PLL)) successfully suppressed bladder tumor growth and induced bladder cancer cell death both in vivo and in vitro [ 84 ].…”
Section: Nanotechnology In Treatmentmentioning
confidence: 99%
“…Hu et al skillfully used block copolymer PEG-b-(PELG-g-(PZLL-r-PLL)) as a nanocarrier to deliver lumbrokinase (LK) with PTX and avoided the great toxicity and ensure sustained release in bladder. In addition, LK/PTX/PEG- b-(PELG-g-(PZLL-r-PLL)) successfully suppressed bladder tumor growth and induced bladder cancer cell death both in vivo and in vitro [ 84 ].…”
Section: Nanotechnology In Treatmentmentioning
confidence: 99%
“…PTX with hydrophobicity property is able to combine PZLL through hydrophobic interaction, thereby enhancement of the half-life and bioavailability of the drugs could be developed via the sustained release and enhancement of tumor site enrichment through passive targeting. They found that (PEG-b-(PELG-g-(PZLL-r-PLL)) polymers prolonged the half-life and bioactivity of LK and PTX in Sprague-Dawley rats [ 155 ]. Tao et al developed increasing delivery efficiency with utilizing different degree of cholesterol substituted pullulan polymer (CHPS).…”
Section: Applications Of Nanomaterials In Treatment Of Bcmentioning
confidence: 99%
“…Its further use to inhibit tumor survival might also be taken into consideration, which means whether lumbrokinase treatment is beneficial for the outcome of tumor patients, especially NSCLC patients, deserves exploration. Several studies have indicated that lumbrokinase could inhibit the growth and metastasis of bladder cancer, gastric cancer, and hepatoma cells in vitro and in animal models [33], although it is still in the early stages of research. Furthermore, considering that the anticoagulant effect of lumbrokinase might possibly compensate for the risk of thrombosis caused by bevacizumab treatment in NSCLC patients, and its natural source, low toxicity, and certain anti-tumor activity might also possibly neutralize the toxic and side effects of chemotherapeutics and delay or weaken the emergence and development of chemoresistance, the potential of the combined treatment strategy including lumbrokinase and bevacizumab or lumbrokinase and chemotherapy might be highlighted for NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%